2021
DOI: 10.12688/f1000research.28142.1
|View full text |Cite
|
Sign up to set email alerts
|

MIREyA: a computational approach to detect miRNA-directed gene activation

Abstract: Emerging studies demonstrate the ability of microRNAs (miRNAs) to activate genes via different mechanisms. Specifically, miRNAs may trigger an enhancer promoting chromatin remodelling in the enhancer region, thus activating the enhancer and its target genes. Here we present MIREyA, a pipeline developed to predict such miRNA-gene-enhancer trios based on an expression dataset which obviates the need to write custom scripts. We applied our pipeline to primary murine macrophages infected by Mycobacterium tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In M0 macrophages 10 miRNAs were differentially expressed (DE) in at least one time point compared to the state before infection (0h), in M1 there was no DE miRNA, while in M2 only Mir1956 was DE. Figure 2 and Table S1 (Extended data 43 ) represent detected miRNA-enhancer-gene trios for M0 macrophages (Extended data: Table S2 for M2 macrophages 43 ). We investigated the functions of the obtained genes and miRNAs and confirmed that many of them might be involved in the response to Mtb infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In M0 macrophages 10 miRNAs were differentially expressed (DE) in at least one time point compared to the state before infection (0h), in M1 there was no DE miRNA, while in M2 only Mir1956 was DE. Figure 2 and Table S1 (Extended data 43 ) represent detected miRNA-enhancer-gene trios for M0 macrophages (Extended data: Table S2 for M2 macrophages 43 ). We investigated the functions of the obtained genes and miRNAs and confirmed that many of them might be involved in the response to Mtb infection.…”
Section: Resultsmentioning
confidence: 99%
“…Zenodo: MIREyA: Extended data, http://doi.org/10.5281/zenodo.4549445. 43 This project contains the following extended data:…”
Section: Extended Datamentioning
confidence: 99%